Entrepreneurs' innovativeness in the South African new business ventures. - Sithole, Clive Bheka (My University, 2017)
Innovation and entrepreneurship are two interrelated concepts that have become an area of interest for many economies. The reasons for such interest are as a result of a realisation of the benefits of entrepreneurship and innovation to the economy. South Africa’s level of entrepreneurship is considered to be quite low when compared to other African countries. This includes the level of innovativeness. Considering the above mentioned context, the main purpose of this research was to investigate innovation in South African Small Medium Enterprises. Through the utilisation of a qualitative research technique, the study analysed the level of entrepreneurs’ innovativeness in South African new business ventures. The research also aimed to understand the potential impact of innovation and determine the factors which increase and inhibit innovation within SA SMEs. In line with the chosen qualitative paradigm, respondents of this research were 14 SME owners / entrepreneurs from the Gauteng region. These were selected through purposive sampling. Face to face semi-structured interviews with the participants were utilised as the research instrument. The data gathered from the interviews was analysed through the method of content analysis. Findings of the research indicate a good understanding and implementation of innovation in South African SMEs. Furthermore, there are various types of innovation which exist within these SMEs. These include process, incremental and product innovation. However, it is important to note the disruptive innovation is still lagging behind as most of the entrepreneurs would rather emulate existing ideas instead of creating new ideas. Factors which influence innovation in SMEs include technology, changing customer needs, resource optimisation and the need to implement best practices. The key limitations of innovation were identified as shortage of skills and funding, labour relations issues, risk associated with innovation and lack of policy support. The impacts of innovation include improved turnover, enhanced business reputation and competitiveness. In as much as South Africa might still be lagging behind in terms of the generic entrepreneurship, there is strong evidence of innovation implementation within some SMEs and willingness to innovate. A concerted effort is required from all the relevant stakeholders to create a supportive environment underpinned by a sound policy framework. This includes addressing the skills gap and providing the required funding for innovation to thrive.
MBA Thesis
Keywords: Small business,New business enterprises -- South Africa,Technological innovations -- Management,Entrepreneurship -- South Africa